Manejo agronómico del cultivo de marañón (Anacardium occidentale) - Puga Morla, Yamilet María (2023)
This document addressed the topic of agronomic management of the cashew crop (Anacardium occidentale). and its effect on the performance and quality of its texture in consumption. This type of crop is produced in Ecuadorian territory. because it presents anomalies that affect this type of crop. Preserve natural resources and increase the profitability of farmers, given that there are numerous factors that influence both the productivity of crops and the quality and nutritional value of this fruit, however, the main objective is to describe the agronomic management of the crop. Cashew nut (Anacardium occidentale). A methodology was carried out with updated data. Furthermore, to prepare this document, information was sought in updated texts, web pages, magazines, scientific articles, virtual libraries and all valuable bibliographic material for the development of this research. The results obtained regarding the agronomic management of cashew cultivation are used mainly for the purpose of preventing soil erosion and improving the appearance of peripheral areas; current production is insufficient to satisfy this demand in global and local markets. It was concluded that it is essential to maximize economic benefits and promote food security. By applying practices such as suitable site selection, efficient water management, proper fertilization and pest and disease control, it is recommended to diversify income sources and establish a gradual approach in adopting innovative technologies in cashew cultivation.